PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN PUBLIK, DAN KEPEMILIKAN ASING TERHADAP KINERJA PERUSAHAAN - Hadi Tjahjadi, FX Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to examine empirically the influence of managerial ownership, public ownership, foreign ownership toward firm performance. Population of this research is manufacturing industries category of consumer goods listed on Indonesia Stock Exchange during 2013-2017. Using purposive sampling technique, 160 manufacturing companies category of consumer goods listed on Indonesia Stock Exchange are selected as sample. The method of analysis was multiple linear regression. The result shows that there is positive effect between managerial ownership and foreign ownership with firm performance. While public ownership has no effect on firm performance.